Building your digital DNA : featuring case studies from : Alliance Boots, We Are Social, Barclays, British Airways, Deloitte Digital, Virgin Media, Facebook, Marks & Spencer, Evening Standard : Lessons from digital leaders.: featuring case studies from : Alliance Boots, We Are Social, Barclays, British Airways, Deloitte Digital, Virgin Media, Facebook, Marks & Spencer, Evening Standard : Lessons from digital leaders. ([2014]) - Unknown
No abstract available